How Well Does a Single Index Represent the Nineteen Sandilands Plant and Machinery Indices? - Peasnell, K. V.; Skerratt, L. C. L. (Journal of Accounting Research, 1977)
In recent years, there has been a growing recognition of the inadequacies of historical cost accounting and of the need to move toward a current value system. An important development in this process was the publication in the United Kingdom of the report of the Inflation Accounting Committee chaired by F. E. P. Sandilands. This report recommends: Accounts drawn up in accordance with the principles of Current Cost Accounting [CCA] should as soon as practicable become the basic published accounts of companies.' The Committee advocated index numbers as a principal method of revaluing plant, machinery, stocks, and work in progress. The purpose of this paper is to present some empirical evidence concerning the commonality among the set of nineteen official government price indices of capital expenditure on plant and machinery2